(untitled) (Cadernos de Sociomuseologia, 2021)
Between the years 1988 and 1996 the Northeastern Museology Forums were held. This irruption movement, which denounces a rupture with the museology practiced by part of the southern region of the country, produced the Manifests and an array of papers that document the memory of eight northeastern Museology meetings. Throughout those, it was possible to investigate how the assertion and recognition relations between the Northeast and Southeast have happened in the sociological construction of the Brazilian Museology field. Using discourse analysis as a methodology resource, I problematized the Brazilian museology field and its narrative, as well as investigated the production and participation of northeastern agents in the construction of the scientific and cultural fields in Brazil. The hypothesis, which was confirmed, was that in the dispute for scientific capital, there were actions that dimmed the importance of the northeastern achievements, culminating in the erasing of research papers from UFBA, FUNDAJ, and other museum institutions of the Northeast in the consolidation of the field. Keywords: field, museology in Brazil, internal colonialism, northeastern, northeastern museology forums.